Implementasi Akad Mudharabah dan Murabahah dalam Pembiayaan Syariah di Indonesia: Tinjauan Fikih Muamalah Kontemporer - Thalib, Afrah; Fauziah Nur Aini (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The development of Sharia financial institutions in Indonesia has seen significant increase over the last two decades, especially in the use of financing contracts in accordance with the principles of Fiqh Muamalah. However, the literature and regulatory reports show that there is an imbalance in the implementation between the profit-sharing-based contract and the buy-and-sell-based contract. Murabahah dominates more than 60-70% of the financing portfolio, while Mudharabah is actually decreasing even though it is ideally considered to reflect the basic value of Islamic finance. This research aims to analyze the implementation of the two contracts from the perspective of Contemporary Muamalah Fiqh, especially regarding sharia compliance issues, transaction risks, and their relevance to the needs of modern financial institutions. The research method used is qualitative with a literature study approach to the DSN-MUI Fatwa, classical and contemporary Fiqh books, OJK and Bank Indonesia reports, as well as national and international scientific journals. The analysis is carried out through content analysis and comparison between the provisions of fiqh with the actual practices of Sharia financial institutions. The findings show that implementating Mudharabah faces challenges including information asymmetry, moral hazard, and practices that shift from the principle of profit sharing to revenue sharing. Meanwhile, although Murabahah is dominant, it is still vulnerable to the issue of tawarruq munazhzham, the lack of real ownership of the bank over the object of goods, and the implementation of late fines. This research confirms the need to strengthen sharia compliance through regulation, contract innovation, and increasing economic fiqh literacy for all parties